2012
DOI: 10.2478/v10015-011-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

More On the Voicing of English Obstruents: Voicing Retention vs. Voicing Loss

Abstract: In Gonet (2010), one of the present authors found out that English word-final phonologically voiced obstruents in the voicing-favouring environment exhibit asymmetrical, if not erratic, behaviour in that voicing in plosives is most often retained while in fricatives voicing retention concerns only about 1/3 of the cases, with the other possibilities (partial and complete devoicing) occurring in almost equal proportions. The present study is an attempt at exploring the intricacies of devoicing in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…They found that increasing values of VOT were primarily tied to the place of stop articulation moving backwards through the oral cavity, which could have implications for understanding why devoicing is more common in certain sonorant consonants in some languages than in others. Finally, Gonet and Święciński (2012) have shown that stress is another factor to consider, as VOT values tended to be higher in stressed syllables.…”
Section: Introductionmentioning
confidence: 95%
“…They found that increasing values of VOT were primarily tied to the place of stop articulation moving backwards through the oral cavity, which could have implications for understanding why devoicing is more common in certain sonorant consonants in some languages than in others. Finally, Gonet and Święciński (2012) have shown that stress is another factor to consider, as VOT values tended to be higher in stressed syllables.…”
Section: Introductionmentioning
confidence: 95%